Improving Fantasy Story Reading Skills Using the SQ3R Method in Grade VII Students of SMP Negeri Satu Atap 5 Dusun Utara - Widiapuspita Widiapuspita; Kastam Syamsi (Journal of Educational Sciences, 2026)
The background of the research is the process of learning Indonesian language in SMP Negeri Satu Atap 5 Dusun Utara class VII using the lecture method and low learning outcomes of Indonesian language. The study aims to describe the improvement of the process and learning outcomes using the SQ3R Method on fantasy story reading skills in Indonesian language learning (Survey, Question, Read, Recite, and Review) for Class VII Students of SMP Negeri Satu Atap 5 Dusun Utara. The research is a classroom action research at SMP Negeri Satu Atap 5 Dusun Utara. The research subjects were class VII students consisting of 17 students. The research consists of 2 cycles consisting of four stages, namely planning, implementation, observation, and reflection. The data collection techniques used were observations, and interviews. The results of the study were: 1) At the pre-action, students' skills in reading fantasy stories in Indonesian language learning had a completion percentage of 0%, 2) At the cycle 1, students' skills in reading fantasy stories in Indonesian language learning had a completion percentage of 41%, and 3) At the cycle 2, students' skills in reading fantasy stories in Indonesian language learning had a completion percentage of 100%.